The adventures of Beekle the unimaginary friend - Santat, Dan 1975- (Little, Brown & Co., 2014)
An imaginary friend waits a long time to be imagined by a child and given a special name, and finally does the unimaginable--he sets out on a quest to find his perfect match in the real world
Keywords: Imaginary companions / Juvenile fiction; Friendship / Juvenile fiction; Imaginary playmates / Fiction; Friendship / Fiction; Picture books for children; Friendship; Imaginary companions